The histone demethylase Phf2 acts as a molecular checkpoint to prevent NAFLD progression during obesity - Julien Bricambert (Nature Portfolio, 2018)
Steatosis is characterized by initial accumulation of lipids, followed by inflammation and ultimately fibrosis. Here the authors show that the histone demethylase Plant Homeodomain Finger 2 protects liver form steatosis progression by acting as a co-activator of ChREBP, thus, favouring lipid accumulation without inflammation.